Health related quality of life of people living with HIV/AIDS on 2nd line Anti Retroviral Therapy (ART) - Senthil Kumar; BWC, Sathiyasekaran (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2017)
Background: HIV/ AIDS is a fast spreading communicable disease and management of the disease has its own challenges. The current treatment strategies are based on 2nd line ART and considering the duration of the illness and risk of several other opportunistic infections, the health related quality of life is a major concern. We aimed to assess the HRQOL among the HIV/AIDS patients on 2nd line ART.Methods: This study was carried out as a cross sectional study among 334 adults visiting the ART center at Chennai. WHOQOL-BREF questionnaire was used to assess the health related quality of life. Statistical analysis was carried out using SPSS version 16 software.Results: The mean age of the study participants was 40.3 years. In this study, 6.9% were separated and 36.2% belonged to upper lower socioeconomic class. The mean score of QOL was highest for the spiritual domain, being 85.14, while the lowest score was observed with social relationship.Conclusion: This study elucidates the importance of social and societal component in the management of HIV/AIDS. The management of the disease should stress further on creating awareness and counseling, to not only the PLHAs but also to their first circle of family/ friends in order to improve their quality of life.